A simple methodology to predict heating load at an early design stage of dwellings - Carlos, Jorge Manuel da Silva (2012)
This paper compares several different simplified methodologies for building energy performance assessment during winter time selected based on its large application and/or its user friendly characteristics. Hourly values for energy demand are calculated by a detailed comparison tool based on hourly weather data. A simplified building procedure spreadsheet to evaluate energy demand is also presented. It gives reliable results, needs only a little input data to describe the building design and low time consumption. The spreadsheet is therefore useful for preliminary design tasks in the early design stages where rough estimates of the building design and preliminary energy use are needed for primary decision support. The method is based on a seasonal heating calculation of heat losses and usable heat gains for the building, where the heat-accumulating capacity of the building is considered. The seasonal mean values of the solar radiation and degree days are applied. This paper describes the applied calculation technique and the assumptions made to carry out heating calculation.